Peranan Kearifan Budaya Lokal Pada Gelahang untuk Mewujudkan Akuntabilitas Pengelolaan Keuangan Upacara Ngenteg Linggih lan Ngusaba Desa Adat Tunju - Dewi, Putu Lusiana; Atmadja, Anantawikrama Tungga (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This research has a purpose: (1) the source of funds for the ngenteg linggih lan ngusaba desa ritual in the Tunju village, (2) accountability of financial management of the ngenteg linggih lan ngusaba desa ritual in the Tunju village, and (3) the role of local cultural wisdom pada gelahang for realizing accountability of financial management ngenteg linggih and ngusaba desa ritual in the Tunju village. Data collection techniques are carried out by conducting observations, interviews and documentation studies. The result show that (1) the source of funds for the ngenteg linggih lan ngusaba desa ritual fund came from dana peturunan, special financial assistance, dana punia, sesari and the sale of t-shirts and pekir as well as the proceeds from the sale of t-shirt and pekir, (2) the process of financial management of ngenteg linggih lan ngusaba desa ritual through the three stages are planning, implementation and evaluation in which there is accountability from the commmite, (3) the role of local cultural wisdom pada gelahang able togetherness, a sense of mutual ownership, mutual trust and strong integration between prajuru desa, commite and village manners in accountability for financial management of ngenteg linggih lan ngusaba desa ritual in the Tunju village.